Tracing the Active Phase and Dynamics for Carbon Nanofiber Growth on Nickel Catalyst Using Environmental Transmission Electron Microscopy. Issue 6 (28th April 2022) - Lyu, Yiqiang; Wang, Peng; Liu, Dongdong; Zhang, Fan; Senftle, Thomas P.; Zhang, Guanghui; Zhang, Zhenyu; Wang, Jianmei; Liu, Wei
Abstract: Benefitting from outstanding ability of CC reforming and hydrogen activation, nickel is widely applied for heterogeneous catalysis or producing high‐quality carbon structures. This high activity simultaneously induces uncontrollable carbon formation, known as coking. However, the activity origin for growing carbon species remains in debate between the on metallic facets induction and nickel carbide segregation. Herein, carbon growth on Ni catalyst is tracked via in situ microscopy methods. Evidence derived from high‐resolution transmission electron microscopy imaging, diffraction, and energy loss spectroscopy unambiguously identifies Ni3 C as the active phase, as opposed to metallic Ni nickel or surface carbides as traditionally believed. Specifically, Ni3 C particle grows carbon nanofibers (CNF) layer‐by‐layer through synchronized oscillation of tip stretch and atomic step fluctuations. There is an anisotropic stress distribution in Ni3 C that provides the lifting force during nanofiber growth. Density functional theory computations show that it is thermodynamically favorable for Ni3 C to decompose into Ni and surface‐adsorbed carbon. Carbonaceous deposits aggregate asymmetrically round the particle because partial surface is exposed to the hydrocarbon environment whereas the bottom side is shielded by the support. This induces a carbon concentration gradient within the particle, which drives C migration through Ni3 C phase before it exits as CNF growth. Abstract : Nickel dynamically transforms into Ni3 C in catalyzing the carbon nanofiber growth. This holistic carbide phase directly contributes to its activity, but not as traditionally believed for Ni or surface carbide layer. On the opposite sides of one Ni3 C particle, two processes simultaneously occur, the Ni carburization by hydrocarbons and Ni3 C decomposition. It forms the carbon gradient inside Ni3 C to drive C migration before it exits as nanofiber/graphite growth.